Future Trends in Genetic Research and Their Implications for Public Health: A Literature Review - Orlova, Iryna; Abramchuk, Olha; Babik, Ivanna; Borysiuk, Iryna; Dats-Opoka, Marta (Futurity Medicine, 2024)
The development of medical genetics, which took place in the last decade, allows specialists to apply an individual approach to treatment considering the genetic characteristics of the patient Aims: to conduct an analysis of the literature on the development of medical genetics and the use of its directions in diagnosis and treatment, as well as to clarify the ethical aspects of the introduction of genetics tools in medicine Methodology: During the literature review, data analysis and summarization was carried out on the topic of the study using the PubMed medical search engine. The search for literary sources was limited to keywords on the research topic and covered the period 2019-2024. Results: As a result of studying the literature, it was established that today the use of medical genetics methods is a promising direction that opens opportunities for the introduction of personalized medicine. Areas such as sequencing and genomics make it possible to study the structural and functional features of the patient's gene and help predict the development of genetic diseases, while pharmacogenomics and bioinformatics make it possible to model the effect of drugs. Scientific Novelty: During the literature search, it was found that the implementation of medical genetics in treatment and diagnostics creates several issues related to the protection of personal data, as well as imperfect sequencing methods can cause diagnostic errors. It is important to ensure access to medical genetics methods for all population groups. Conclusion: today society is on the threshold of a discovery in medicine, which relates to the introduction of medical genetics tools in diagnosis and treatment. The methods make it possible to treat a specific patient considering genetic characteristics, which improves diagnosis, reduces the side effects of drugs and, in general, improves the results of treatment.